2011
DOI: 10.1044/1058-0360(2011/09-0005)
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Production Frequency in Therapy for Childhood Apraxia of Speech

Abstract: Both treatment designs were effective, though frequent and intense practice of speech resulted in more rapid response to treatment in 2 children whose primary communication difficulty was childhood apraxia of speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 46 publications
(57 reference statements)
4
62
1
2
Order By: Relevance
“…Although some studies reported findings consistent with the motor learning literature [14••,41,47], others failed to find clear and consistent differences between conditions [42,43,45,51,52], or reported opposite effects for some participants [22•,44]. It is likely that differences in tasks, measures, and populations contribute to this mixed pattern.…”
Section: Speech Motor Control and Learningmentioning
confidence: 97%
See 2 more Smart Citations
“…Although some studies reported findings consistent with the motor learning literature [14••,41,47], others failed to find clear and consistent differences between conditions [42,43,45,51,52], or reported opposite effects for some participants [22•,44]. It is likely that differences in tasks, measures, and populations contribute to this mixed pattern.…”
Section: Speech Motor Control and Learningmentioning
confidence: 97%
“…In the last 15 years, incorporation of motor learning principles into treatment for CAS has been recommended [12–18]. Several published treatment studies have implemented some of these principles [12,19–20], but few studies have systematically compared practice conditions in CAS treatment [14••,2122•]. In this section, we briefly review important concepts and trends in extending this research paradigm to examining its relevance for enhancing speech motor learning.…”
Section: Speech Motor Control and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain and Hoyson (2000) offered one of the only discussions of intervention intensity related to the implementation of a social-pragmatic (developmentally based) communication approach for a child served in a preschool classroom setting. Recently, several investigations manipulated parameters of dosage in a range of curricular areas that involve content areas that are outside the content parameters of this investigation (e.g., Bellon-Harn, 2012;Brady & Bashinski, 2008;Breit-Smith et al, 2009;Edeal & Gildersleeve-Neumann, 2011;Smith-Lock et al, 2013; see also Fey, Yoder, Warren, & Bredin-Oja, 2013).…”
Section: Preliminary Examinations Of Treatment Intensity (Dosage) Commentioning
confidence: 98%
“…By comparison, ES for single-subject design is just beginning to be extended to clinical populations and treatment. Research in the area of aphasia (Beeson & Robey, 2006;Robey, 1994Robey, , 1998Robey, Schultz, Crawford, & Sinner, 1999) has led the way with complementary data emerging, for example, in treatment of autism/ developmental disability (Olive & Smith, 2005), childhood apraxia of speech (Edeal & Gildersleeve-Neumann, 2011), learning disability (Swanson & Sachse-Lee, 2000), and phonological disorders in children (Gierut & Morrisette, 2011).…”
mentioning
confidence: 99%